Upaya Hukum Terhadap Perkawinan Orang Dalam Gangguan Jiwa - Zulhizah Febriansyah; Lalu Hadi Adha (Private Law, 2022)
The objective of this study is to examine the position of marriages carried out by people with mental disorders and to determine the legal remedies taken against marriages of people with mental disorders. The type of research used within this study is normative research. Based on the results of the study, the marital position of people with mental disorders is invalid because they do not meet the pillars and conditions of marriage. Legal remedies taken against marriages of people with mental disorders are regulated in Law Number 1 of 1974 Concerning Marriage, Law Number 16 of 2019 amendments to Law Number 1 of 1974 Concerning Marriage, Law Number 7 of 1989 Concerning Religious Courts, Presidential Instruction of the Republic of Indonesia Number 1 of 1991 Concerning Complications of Islamic Law, namely: marriage preventionand marriage annulment.